Detección de Alfa 1-antitripsina e Iinterleucina-8 en pacientes con Meningitis - Abbas, Samir K.; Iqbal, Mayada N.; Abdul Majeed, Nahlah G. (Innovaciencia, 2019)
Meningitis is a meninges inflammation and the subarachnoid cerebrum spinal fluid that surrounds the spinal cord and brain. Infantile meningitis is a major cause of morbidity & mortality in various parts of the world; it is earnest disorder owing to the nearness of the location to the brain and spinal cord. It can be caused by virtually any organism; in general viral infections are more common than bacterial, fungal and parasitic infections respectively. Objective: investigation of the Interleukin-8 (IL-8) and Alaph-1 Antitrypsin in the cerebrum spinal fluid of meningitis patients. Material and Method: A study was done at the Medical city and Al-kadimia hospitals included 47 and 20 beings of Patients and Control groups with an overall age range between 11 days to 6 years old. According to the causative agents of the disease, they were divided into three groups: bacterial, viral and control groups. All subjects were monitored for the IL-8 by Enzyme Linked Immunosorbent Assay (ELISA) and Alaph-1 Anti-trypsin by Single Radial Immunodiffusion assay (SRIA) in the cerebrospinal fluid the data was analyzed via using SPSS (chi-squire test) program (version 22). Results and discussion: The results revealed the presence of an elevation concentration of IL-8 among meningitis disease patients (484.0695 pg/ml ), high concentration of IL-8 seemed in bacterial meningitis (825.3250pg/ml) when compared with its level in viral meningitis (142.8143pg ml) ( p= 0.002) and control group ( 56.3409 pg/ml) (p=0.00) but no significant difference was found between viral and control groups (p= 0.679). Alpha 1 antitrypsin results appeared high concentration of (21.6462 mg/ dl) and (16.4000 mg/ dl) in bacterial and viral meningitis groups in sequentially, and that concentrations showed differences arrived significantly. The statistical analysis of this research showed a correlation between IL-8 levels and both of neutrophil and lymphocyte in meningitis patients. IL-8 had significant correlation with lymphocyte (p=0.02) in viral group while no significant correlation was appeared between IL-8 and neutrophil. In bacterial group, lymphocytes with IL-8 had weak correlation, in contrary the correlation between neutrophil and IL-8 revealed the significantly correlation (p=0.01). No correlation was establish concerning the Alpha-1 antitrypsin and the cell’s numbers and types. Conclusion: A study indicated that Alpha 1 antitrypsin and IL-8 played an important role in meningitis disease.